Utilization of injury care case studies: a systematic review of the World Health Organization’s “Strengthening care for the injured: Success stories and lessons learned from around the world” (2018)
Objective Translation of evidence to practice is a public health priority. Worldwide, injury is a leading cause of morbidity and mortality. Case study publications are common and provide potentially reproducible examples of successful interventions in healthcare from the patient to systems level. However, data on how well case study publications are utilized are limited. To our knowledge, the World Health Organization (WHO) published the only collection of international case studies on injury care at the policy level. We aimed to determine the degree to which these injury care case studies have been translated to practice and to identify opportunities for enhancement of the evidence-to-practice pathway for injury care case studies overall. Methods We conducted a systematic review across 19 databases by searching for the title, “Strengthening care for the injured: Success stories and lessons learned from around the world.” Data synthesis included realist narrative methods and two authors independently reviewed articles for injury topics, reference details, and extent of utilization. Findings Forty-seven publications referenced the compilation of case studies, 20 of which included further descriptions of one or more of the specific cases and underwent narrative review. The most common category utilized was hospital-based care (15 publications), with the example of Thailand’s quality improvement (QI) programme (10 publications) being the most commonly cited case. Also frequently cited were case studies on prehospital care (10 publications). There was infrequent utilization of case studies on rehabilitation (3 publications) and trauma systems (2 publications). No reference described a case translated to a new scenario. Conclusions The only available collection of policy-level injury care case studies has been utilized to a moderate extent however we found no evidence of case study translation to a new circumstance. QI programs seem especially amenable for knowledge-sharing through case studies. Prehospital care also showed promise. Greater emphasis on rehabilitation and health policy related to trauma systems is warranted. There is also a need for greater methodologic rigor in evaluation of the use of case study collections in general.